A comparison between in situ monazite Lu–Hf and U–Pb geochronology - A. T. De Vries Van Leeuwen; A. T. De Vries Van Leeuwen; A. T. De Vries Van Leeuwen; S. Glorie; S. Glorie; M. Hand; M. Hand; J. Mulder; S. E. Gilbert (Geochronology)
In complex metamorphic rocks, monazite U–Pb dates can span a wide concordant range, leading to ambiguous geological interpretations (e.g. slow protracted cooling versus multiphase growth). We present in situ monazite Lu–Hf analysis as an independent chronometer to verify U–Pb age interpretations. Monazite Lu–Hf dates were attained via laser ablation inductively coupled plasma mass spectrometry equipped with collision/reaction cell technology (LA-ICP-MS/MS). In situ Lu–Hf dates for potential reference monazites with uncertainties <1.6 % agree with published U–Pb dates, validating the approach. We demonstrate the method on complex metamorphic samples from the Arkaroola region of the northern Flinders Ranges, South Australia, which exhibit protracted thermal and monazite growth histories due to high geothermal gradient metamorphism. In situ Lu–Hf dates reproduce the main U–Pb monazite age populations, demonstrating the ability to reliably resolve multiple age populations from polymetamorphic monazite samples.